(untitled) (Al-Jabal Journal of Humanities and Applied Sciences, 2024)
Geographic natural and human factors are the primary elements in all developmental plans of any country; they influence various economic activities, including tourism, which relies on these factors. The study aims to identify these natural and human factors in Zintan Municipality that could contribute to the tourism sector in the region. The research is motivated by the potential to make tourism a significant economic alternative, diversifying the municipality’s income sources. Given that Zintan’s economy relies primarily on agriculture and trade, the study seeks to provide new information about the tourism sector through field research.The study employs three research methods: regional, descriptive, and historical. Key findings include that Zintan Municipality possesses tourism-inducing factors that remain untapped and require attention. Additionally, various obstacles hinder the development of this tourism pattern.